2021
DOI: 10.1002/hbm.25735
|View full text |Cite
|
Sign up to set email alerts
|

Negative bias effects during audiovisual emotional processing in major depression disorder

Abstract: Aberrant affective neural processing and negative emotional bias are trait-marks of major depression disorders (MDDs). However, most research on biased emotional perception in depression has only focused on unimodal experimental stimuli, the neural basis of potentially biased emotional processing of multimodal inputs remains unclear. Here, we addressed this issue by implementing an audiovisual emotional task during functional MRI scanning sessions with 37 patients with MDD and 37 gender-, age-and education-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Patients with MDD exhibit decreased ability of retrieval in declarative memory [ 53 , 54 , 56 ], linked to the hippocampal functionality, and recent evidence suggests a dual role of the intermediate hippocampus in memory and affective information processes [ 57 ]. Moreover, MDD is characterized by a processing bias toward the negative aspect of the environment that can be considered a key component in depression [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MDD exhibit decreased ability of retrieval in declarative memory [ 53 , 54 , 56 ], linked to the hippocampal functionality, and recent evidence suggests a dual role of the intermediate hippocampus in memory and affective information processes [ 57 ]. Moreover, MDD is characterized by a processing bias toward the negative aspect of the environment that can be considered a key component in depression [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of included studies are shown in Table 1 . Among 28 included studies, 20 studies ( 17 19 , 40 47 , 49 , 50 , 52 , 53 , 55 , 57 59 , 61 ) were published in English and 8 ( 37 – 39 , 48 , 51 , 54 , 56 , 60 ) were in Chinese. A total of 656 patients with depression and 680 healthy subjects were involved.…”
Section: Resultsmentioning
confidence: 99%
“…The average age of participants ranged from 15 to 66 years old, and only 2 studies ( 40 , 55 ) focused on youths with depression. Depressive patients in 20 studies ( 17 19 , 40 47 , 49 , 50 , 52 55 , 57 , 59 , 61 ) were diagnosed according to the DSM, 1 ( 37 ) in the light of CCMD, and 2 ( 51 , 58 ) based on ICD; 3 studies applied DSM-IV and CCMD-3 ( 38 , 39 , 60 ); 1 used both DSM-IV and ICD-10 ( 56 ); 1 adopted CCMD-3 and ICD-10 ( 48 ). Hamilton Depression Rating Scale, Beck Depression Inventory, Montgomery–Asberg Depression Scale, Center for Epidemiologic Studies Depression Scale, and Children's Depression Rating Scale-Revised were adopted to screen depression.…”
Section: Resultsmentioning
confidence: 99%
“…Cultural diversity may partly account for the discrepancy because this item remains controversial in the Chinese version of the PANAS [ 61 , 62 ], showing moderate correlation with both positive and negative affect. On the other hand, this interesting result may reflect a negative bias effect during emotion processing in MDD [ 63 ]. Consistently, previous evidence has suggested that increased level of alert is associated with anxiety [ 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%